Guru Sadar Lingkungan Berbasis Konsep Tri Hita Karana - Nyoman Wiraadi Tria Ariani; Ida Bagus Komang Sindu Putra; Marsono; Putu Ayu Septiari Dewi; I Gusti Lanang Agung Wiranata (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The Hindu community in Bali who believes and lives by carrying out the Tri Hita Karana concept, provides potential that can be used as a basis for providing education for various levels of education age, one of which is in PAUD education. This potential can be adopted in the implementation of early childhood education. Everything that becomes the implementation of the Tri Hita Karana concept can be used as a medium in providing a stimulus to the development of early childhood. Tri Hita Karana is a basic concept that expects humans to maintain the relationship between the three elements (Parahyangan, Pawongan, and Palemahan) so that they can achieve happiness. The implementation of community service in the form of Environmental Awareness Teacher Skills Development Based on the Tri Hita Karana Concept for PAUD Teachers in the North Denpasar area which was carried out in a span of 5 meetings, starting from May 9 to May 13, 2022. This community service scope includes several activities include: delivery of material and brief discussions on understanding the concept of environmentally conscious teachers based on the concept of Tri Hita Karana, practice of developing activities based on the concept of Tri Hita Karana, movements and songs, as well as performance of the work. The community service that has been carried out has received a very good response and is fully supported by the Kindergarten Supervisor for the North Denpasar area who is also involved as a participant. This is evidenced by the attendance rate of participants at each meeting reaching 100% and the response from the evaluation of activities being very good with the presentation of very useful activities and the demand for the implementation of similar activities on an ongoing basis targeting more PAUD institutions in the Denpasar City area. Keywords: PAUD, Environment, Tri Hita Karana